2020
DOI: 10.1093/eurpub/ckaa165.610
|View full text |Cite
|
Sign up to set email alerts
|

Students as advocates of global health goals: the case of medical education in Germany

Abstract: Background Germany has started to take on greater responsibility in global health policy. Furthermore, new threats, such as climate change, have increased sensitivity. However, health professionals are not well prepared to respond to the new tasks and the changing needs of the population. Global health is still largely missing from the education and training programmes of the vast majority of professional groups in Germany. This paper aims to illustrate how students can become advocates of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Third, we introduce new global health courses which have been developed and accredited between spring term 2019 and autumn term 2020 at Hanover Medical School 25,27,28 . The courses are explored in relation to the substance and the actors and implementation processes 30 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we introduce new global health courses which have been developed and accredited between spring term 2019 and autumn term 2020 at Hanover Medical School 25,27,28 . The courses are explored in relation to the substance and the actors and implementation processes 30 …”
Section: Methodsmentioning
confidence: 99%
“…9 It is important to note that most complex suggestions for strengthening global health in medical education have been introduced, at first and foremost, by the national medical student association and their various representatives over time. [11][12][13]17,18,27,28,[43][44][45][46] These authors have identified a wide range of topics and challenges relevant to global health education, including a health systems approach and the social determinants of health, among others. 46,47 To this end, developments in global health education seem to mirror wider societal movements strongly driven by young people, most prominently known from climate change activism.…”
Section: Where Are We Now? Discourse Strategies and Regulatory Frameworkmentioning
confidence: 99%